Novel Dual COX-2/5-LOX Inhibitory Activity by Chalcone Derivatives: A Safe and Efficacious Anti-inflammatory Agent - Mittal, Roopal; Sharma, Shailesh; Mittal, Amit; Kushwah, Ajay Singh (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2024)
Background Non-communicable diseases are chronic systemic inflammation in humans that occurs because of enhanced inflammatory mediators of the arachidonic acid cascade. We aimed to explore whether the lead chalcone compounds could exhibit anti-inflammatory activity via dual blockage of COX-2/5-LOX enzymes and their regulatory mechanism. Methods RAW 264.7 macrophages were collected from NCC, Pune, for in-vitro experiments. The IC50 values of chalcone compounds C45 and C64 were calculated. RAW 264.7 macrophages were treated with C45 and C64 (10%, 5%, 2.5%, 0.125%, and 0.0625% concentration). The cell viability was carried out with an MTT assay. The COX-1, COX-2, 5-LOX, PGE2, and LTB4 levels were detected by ELISA-based kits. The in-vivo evaluation was carried out in Male Wistar rats (250-300 g, 7-8 weeks old) with acute and chronic anti-inflammatory models and histopathological studies on the stomach, liver, and kidney. Results The present study described the in-vitro and in-vivo biological evaluation of dual COX-2/5-LOX inhibitors in chalcone derivatives (C45 and C64) compounds showed the most effective COX-2 and 5-LOX inhibition with IC50 values 0.092 and 0.136 µM respectively. Simultaneously, compound C64 showed comparable selectivity towards COX-2 with a Selectivity Index (SI) of 68.43 compared to etoricoxib, with an SI of 89.32. In-vivo carrageenan-induced rat paw oedema activity, the compound C64 showed a significant reduction in oedema with 78.28% compared to indomethacin with 88.07% inhibition. Furthermore, cotton pellet-induced granuloma activity revealed that compound C64 significantly reduced 32.85% compared with standard 40.13% granuloma inhibition. Conclusion The chalcone compound C64, (E)-1-(4-Amino-2-hydroxyphenyl)-3-(3,4,5-trimethoxyphenyl)-prop-2-en-1-one was proved to be a potent and novel Dual COX-2/5-LOX inhibitor with improved gastric safety profiling.
Keywords: inflammation